2006
DOI: 10.1016/j.crvi.2006.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Differences in pharmacokinetic and electroencephalographic responses to caffeine in sleep-sensitive and non-sensitive subjects

Abstract: The present study investigated pharmacokinetic and electroencephalographic responses to caffeine (140 mg) in two groups of healthy volunteers reporting, or not, caffeine-related sleep disturbances. Significant differences in caffeine consumption and smoking habits were observed between the two groups. Plasma samples were taken from each subject before (T 0 ) and after caffeine intake at 0.5, 1, 2, 4, 6 and 24 h. Three pharmacokinetic parameters: half-life (t 1/2 ), maximum time (T max ) and maximum plasma conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…However, this possibility was offset by the repeated measures design limiting the effects of intersubject variability related to caffeine sensitivity, absorption, and bioavailability and individual differences in habitual sleep patterns. 44 Another limitation was the small number of subjects assessed in the present study, which may have contributed to reduced power to detect caffeine effects on sleep disturbance using selfreport. Intermittent exposure to caffeine used in the present design precludes us from making any conclusions regarding possible tolerance to the effects observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, this possibility was offset by the repeated measures design limiting the effects of intersubject variability related to caffeine sensitivity, absorption, and bioavailability and individual differences in habitual sleep patterns. 44 Another limitation was the small number of subjects assessed in the present study, which may have contributed to reduced power to detect caffeine effects on sleep disturbance using selfreport. Intermittent exposure to caffeine used in the present design precludes us from making any conclusions regarding possible tolerance to the effects observed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some individuals are susceptible to its anxiogenic effects (Silverman and Griffiths 1992) and others to caffeine-induced sleep disturbances and insomnia (Bchir et al 2006). Caffeine can aggravate anxiety and precipitate panic attacks in patients with anxiety and panic disorder, which often results in decreased consumption in these individuals (Bruce et al 1992; Charney et al 1985; Lee et al 1985; Nardi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported caffeine-induced decreases in the alpha bandwidth, broadly defined as [8][9][10][11][12] Hz [8][9][10][15][16][17][18][19] , but an increase has also been reported [11] , as has no effect [7,12,13] . Effects on power in the beta bandwidth, broadly defined as 12-30 Hz, appear equally inconsistent, with reports of increases [11,18] , decreases [8,10,19] , and no effect [7,12,13,15,16] .…”
mentioning
confidence: 99%
“…In the delta bandwidth, broadly defined as 0-4 Hz, caffeine has been reported to increase [7] , decrease [8][9][10][11] , and to have no effect [12][13][14][15][16] on EEG power within that band. In the theta bandwidth, broadly defined as 4-8 Hz, caffeine has been reported to decrease theta power [8,10,11] and to have no effect [7,[12][13][14][15][16] .…”
mentioning
confidence: 99%
See 1 more Smart Citation